2015
DOI: 10.1007/978-3-319-23117-4_60
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Intra- and Inter-modality Algorithms for Face-Sketch Recognition

Abstract: Abstract. Identifying and apprehending suspects by matching sketches created from eyewitness and victim descriptions to mugshot photos is a slow process since law enforcement agencies lack automated methods to perform this task. This paper attempts to tackle this problem by combining Eigentransformation, a global intra-modality approach, with the Eigenpatches local intra-modality technique. These algorithms are then fused with an inter-modality method called Histogram of Averaged Orientation Gradients (HAOG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…using a linear combination of images, the Eigen-patches (EP) extension [15] performing synthesis at a local level, and the Bayesian framework in [16] that considers relationships among neighbouring patches for model construction. A more thorough review of FH algorithms may be found in [4], [13], [15]- [17].…”
Section: Related Workmentioning
confidence: 99%
“…using a linear combination of images, the Eigen-patches (EP) extension [15] performing synthesis at a local level, and the Bayesian framework in [16] that considers relationships among neighbouring patches for model construction. A more thorough review of FH algorithms may be found in [4], [13], [15]- [17].…”
Section: Related Workmentioning
confidence: 99%
“…Existing face sketch recognition methods can be classified into two categories: intra-modality and inter-modality approaches [2]- [4]. Intra-modality approaches deploy a preprocessing step that synthesizes pseudo sketch from input photo and perform face sketch recognition in the same modality [2], [3], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Existing face sketch recognition methods can be classified into two categories: intra-modality and inter-modality approaches [2]- [4]. Intra-modality approaches deploy a preprocessing step that synthesizes pseudo sketch from input photo and perform face sketch recognition in the same modality [2], [3], [7]. In contrast, inter-modality approaches try to extract more discriminative and modality-invariant features (such as histogram of gradients (HOG) [1]) from input sketch and photo and match them [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations